CONSIDERATIONS CONCERNING THE STATE AID POLICY IN THE CONTEXT OF THE COVID-19 CRISIS IN ROMANIA - Florentina Cristina BÂLDAN; Maria Nicoleta DASCĂLU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
In the paper “Considerations concerning the state aid policy in the context of the COVID-19 crisis in Romania” we briefly presented the main economic measures taken in Romania, in the context of the current crisis, of the role of the competition policy and we highlighted aspects pertaining to the temporary framework of granting state aids and to the situation of the state aids authorised lately.